Changing the home visiting research paradigm: models' perspectives on behavioral pathways and intervention techniques to promote good birth outcomes - Anne K. Duggan; Kelly M. Bower; Ciara Z. Spinosa; Kay O'Neill; Deborah Daro; Kathryn Harding; Allison Ingalls; Allison Kemner; Crista Marchesseault; William Thorland (BMC, 2022)
Abstract Background The US is scaling up evidence-based home visiting to promote health equity in expectant families and families with young children. Persistently small average effects for full models argue for a new research paradigm to understand what interventions within models work best, for which families, in which contexts, why, and how. Historically, the complexity and proprietary nature of most evidence-based models have been barriers to such research. To address this, stakeholders are building the Precision Paradigm, a common framework and language to define and test interventions and their mediators and moderators. This observational study used portions of an early version of the Precision Paradigm to describe models' intended behavioral pathways to good birth outcomes and their stance on home visitors' use of specific intervention technique categories to promote families' progress along intended pathways. Methods Five evidence-based home visiting models participated. Model representatives independently completed three structured surveys focused on 41 potential behavioral pathways to good birth outcomes, and 23 behavior change technique categories. Survey data were used to describe and compare models' intended behavioral pathways, explicit endorsement of behavior change technique categories, expectations for home visitors' relative emphasis in using endorsed technique categories, and consistency in endorsing technique categories across intended pathways. Results Models differed substantially in nearly all respects: their intended pathways to good birth outcomes (range 16-41); the number of technique categories they endorsed in any intended pathway (range 12-23); the mean number of technique categories they endorsed per intended pathway (range 1.5-20.0); and their consistency in endorsing technique categories across intended pathways (22%-100% consistency). Models were similar in rating nearly all behavior change technique categories as at least compatible with their model, even if not explicitly endorsed. Conclusions Models successfully used components of the Precision Paradigm to define and differentiate their intended behavioral pathways and their expectations for home visitors' use of specific technique categories to promote family progress on intended pathways. Use of the Precision Paradigm can accelerate innovative cross-model research to describe current models and to learn which interventions within home visiting work best for which families, in which contexts, why and how.